Emergence of Non-summative Relations in Language (Signifiances (Signifying), 2024)
The appearance of signs is linked to the relationship of a form, which in itself has no semantic value, with a content, to which it is linked by convention. From this result two strong assertions: 1) that the signifier (the form) and the signified (the content) are the two sides of the sign; 2) that the union of the signifier and the signified is arbitrary; a corollary of 1) and 2) is that on both levels new units are produced from the addition of smaller units. Since F. de Saussure formulated this definition of the sign, descriptively easy to manipulate, linguistics has been confirming that there is something more. It consists of non-summative transversal relations, which occur at all levels (words whose meaning leads to other words, phonemes that sound like other phonemes in the chain, etc.). These relations are enactive, they result from the mutual determination of language and world.L’apparition des signes est liée au rapport d’une forme, qui en elle-même n’a aucune valeur sémantique, avec un contenu, auquel elle est liée par convention. De cela résultent deux affirmations fortes : 1) que le signifiant (la forme) et le signifié (le contenu) sont les deux faces du signe ; 2) que l’union du signifiant et du signifié est arbitraire ; un corollaire de 1) et 2) est qu’aux deux niveaux, de nouvelles unités sont produites à partir de l’ajout d’unités plus petites. Depuis que F. de Saussure a formulé cette définition du signe, descriptivement facile à manipuler, la linguistique confirme qu’il y a quelque chose de plus. Il s’agit de relations transversales non sommatives, qui se produisent à tous les niveaux (mots dont le sens mène à d’autres mots, phonèmes qui rappellent d’autres phonèmes de la chaîne, etc.). Ces relations sont énactives, elles résultent de la détermination mutuelle du langage et du monde.